Limnological parameters in Skarvsnes lakes between the 51st and 52nd Japanese Antarctic Research Expeditions in 2010–2011—Long-term monitoring study— - KUDOH, Sakae; TANABE, Yukiko (2015)
Fig. 1, 2 | http://polaris.nipr.ac.jp/~parc/pub/v003/nipr_parc_188_0006.docx departmental bulletin paper